Topical agents for oral cancer chemoprevention: A systematic review of the literature. (April 2017) - Chau, Lucy; Jabara, Justin T.; Lai, Wanda; Svider, Peter F.; Warner, Blake M.; Lin, Ho-Sheng; Raza, S. Naweed; Fribley, Andrew M.
Highlights: Topical agents may be efficacious for oral cancer chemoprevention. Topical agents reduce systemic toxicity and avoid first-pass metabolism. Retinoids, bleomycin, adenovirus, and PDT reduce clinical presence of oral lesions. Need for future randomized controlled trials with longer follow-up. Abstract: Objectives/hypothesis: We review the use of topical chemoprevention agents in patients with oral potentially malignant disorders (PMD). Methods: A systematic review of studies on topical chemoprevention agents for oral PMD from 1946 to November 2016 was conducted using the MEDLINE database, Embase, and Cochrane Library. Data were extracted and analyzed from selected studies including study type, sample size, demographics, treatment length, response rate, follow-up time, adverse effects, and recurrence. Results: Of 108 studies, twenty-four, representing 679 cases met the inclusion criteria. The clinical lesions evaluated included oral leukoplakia, erythroplakia (OEL), verrucous hyperplasia (OVH), oral lichen planus, larynx squamous cell carcinoma, and oral squamous cell carcinoma (OSCC). The mean complete response rate for topical retinoid therapy was 32%. The mean complete response rate for 1% bleomycin therapy and 0.5% bleomycin was 40.2% and 25%, respectively. The complete response rate of OVH, OEL, and OSCC to photodynamic therapy ranged from 66.7% to 100%. Conclusion: There are a paucity of data examining topical treatment of oral PMDs. However, the use of topical agents among patients with oral lesions may be a viable complement or even alternative to traditional surgery, radiation, or systemic chemotherapy, with the advantage of reducing systemic side effects and sparing important anatomic structures. This study of 679 cases represents the largest pooled sample size to date, and the preliminary studies in this systematic review provide support for further inquiry.